Construcción de la identidad sexual en la novela y película "El Beso de la Mujer Araña" - Mayora Soldevilla, Milia, author; Valerio-Holguín, Fernando, advisor; López-Cabrales, María del Mar, committee member; Velasco, Marcela, committee member (Colorado State University. Libraries, 2014)
Kiss of the Spider is one of the most studied novels of Latin American literature since its publication. Its wide acceptance among readers and critics encouraged Héctor Babenco to adapt the novel into a film that would win many international awards. Despite these awards, the adaptation has not been studied as thoroughly as the novel, which is why in this work I will try to study which elements from the novel Babenco deleted when adapting it into the movie and what he chose to replace them with. It is intended, first, to study the construction of Molina's sexual identity in the novel and discuss the oppositions of male/female, masculinity/femininity, etc., and, then, to see how Babenco does it in the film, because it deletes one of the main elements of the novel that allows the construction of sexual identity: the bolero. Second, I will discuss the possible double meaning of one of the elements that Babenco chooses to replace. Considering that the political situation in which both the novel and the movie were created was similar, he makes a political statement and complaint.
Constructing sexual identity in the novel and movie Kiss of the Spider Woman